Evaluation of coupled porewater pressure and stress-strain constitutive model in granular soils (2018)
The evaluation of performance of three coupled pressure (PWP) generation models and stress-strain constitutive models are applied to granular soils. Those constitutive models are used to recommend them for subsequent application in seismic site-response analysis in effective stresses. The performance of the three-coupled models were evaluated using a database of 25 selected high quality cyclic simple shear tests. The conducted analysis suggested that the simple Coupled GMP and stress-strain constitutive model reasonably capture PWP behavior observed in the laboratory tests, they are analyzed better than using advanced constitutive models, and all of them can be used to perform effective stress-based one-dimensional site-response analysis.